Priorities for the rural water and sanitation services regulation in Latin America - Alvarez, Lourdes; Vargas, Laura; Jimenez, Alejandro (Frontiers in Water, 2024)
In 2022, 65.1% of people without access to at least basic water services and 44.6% of people without access to at least basic sanitation services in Latin America and the Caribbean (LAC) lived in rural areas. Addressing the disparity of access to drinking water, sanitation and hygiene (WASH) services requires appropriate and differentiate regulation for rural areas. This paper presents the results of a research and consultation process, with more than 80 experts in governance and WASH from 14 regulators and other WASH institutions in LAC on regulatory priorities for rural areas in the region. The 11 priorities identified are related to the development of rural services governance, support to rural service providers and users’ role. These priority areas include the formalization and association of providers, the definition of specific service delivery standards for rural areas, the design of subsidies and non-economic incentives, training and technical assistance to providers, inter-institutional coordination and peer learning, information reporting, integrated management of water resources, and the promotion of user’s participation and accountability, behavioral change programmes, gender equity and an intercultural approach. While promising experiences are presented in all areas, we propose that collective action is required to transform rural WASH regulation into a supportive, collaborative and integrative function that improves quality access to sustainable and resilient WASH services in the region.